Nordic Seas polynyas and their role in preconditioning marine productivity during the Last Glacial Maximum - Jochen Knies (Nature Communications, 2018)
Polynyas potentially played a role in sustaining marine life during the last glacial, yet their presence and importance remains equivocal. This multi-proxy study reconstructs a corridor of polynyas in the Nordic Seas during the last glacial maximum, and reveals a strong association with biological productivity.